The Balance of Th1/Th2 and LAP+Tregs/Th17 Cells Is Crucial for Graft Survival in Allogeneic Corneal Transplantation - Shang Li; Jing Yu; Chungang Guo; Ying Jie; Zhiqiang Pan (Journal of Ophthalmology)
Purpose. CD4+LAP+ T cells are newly discovered regulatory T cells (Tregs). The aim of this study is to investigate the balance of Th1/Th2 and LAP+Tregs/Th17 in mice after allogeneic corneal transplantation. Methods. A total of 65 mice received orthotopic penetrating transplantation. According to the survival scores of the grafts, the mice were divided into the rejection group and the survival group 3 weeks after transplantation. Th1, Th2, Th17, and regulatory T cells in the ipsilateral drainage lymph nodes and spleens were measured with flow cytometry. The related cytokines in aqueous humor were also analyzed. Results. The frequencies of Foxp3+Tregs, GARP+Tregs, and LAP+Tregs in the survival group were significantly higher than those in the rejection group. And the expression trend of CD4+LAP+ T cells and CD4+GARP+ T cells was consistent. The level of IFN-γ, TNF, IL-6, and IL-17A markedly increased in aqueous humor during corneal allograft rejection. The ratio of Th1/Th2 and Th17/LAP+Tregs significantly increased in the rejection group at the 3rd week after corneal transplantation. Conclusion. LAP+Tregs might be regarded as substitute for Foxp3+Tregs. The balance of Th1/Th2 and LAP+Tregs/Th17 is crucial for corneal allograft survival.